Global health collaborative research: beyond mandatory collaboration to mandatory authorship - Wongani John Nyangulu (BMC, 2023)
Abstract Collaborative research between the global north and global south is common and growing in number. Due to inability of local governments to fund research, global north actors provide the bulk of research funding. While providing mutual benefits, global collaborative research projects are far from ideal. In this paper, we review the authorship discrepancies in global collaborative research, discuss preventive measures in place and their shortfalls, and recommend an intervention to address the problem. Malawi research guidelines recommend collaboration between foreign and local researchers in locally conducted research. However, there is no provision requiring joint authorship in final published papers. Journal recommendations on authorship criteria exist, but they can disadvantage low- and middle-income country researchers in collaborative projects because of exclusionary interpretations of guidelines. For example, the requirement for authors to make substantial contributions to conception or design of the work may favor research grant holders, often from the global north. Systematic and holistic changes proposed to address power asymmetries at the core of the problem have been proposed. However, these proposals may take a long time to produce change. Ad interim, local institutions can take more direct action to address inequalities by establishing offices of research integrity to enforce mandates to increase opportunities for authorship in collaborative research.